Analisis Efektivitas Biaya Seftriakson sebagai Antibiotik Profilaksis Pada Seksio Sesarea: Dosis Tunggal Versus Dosis Berulang - Bayu Pertiwi; Hesty Utami Ramadaniati; Prih Sarnianto; Dwirani Amelia (Fakultas Farmasi Universitas Pancasila, 2022)
The provision of single-dose prophylactic antibiotics within 30 to 60 minutes before caesarean has been highly recommended, yet its implementation in hospitals varies considerably. This research aimed to analyze the cost-effectiveness of prophylactic antibiotics given a single dose versus multiple doses during caesarean section surgery. A retrospective observational study with a crosssectional design involved pregnant women undergoing caesarean section and receiving a ceftriaxone single dose before surgery (Group 1) versus those receiving multiple ceftriaxone doses (Group 2). The study calculated direct medical costs (hospital perspective), with surgical site infection (SSI) as the effectiveness parameter. The chi-square test was used to compare SSI between the two groups. There were 806 patients (group 1) and A total of 250 patients (Group 2) met the inclusion criteria. Analysis of total cost revealed no significant difference between both groups (approximately IDR 13,000,000/patient), yet patients receiving prolonged Ceftriaxone were associated with significantly higher antibiotic costs (p-0.000). The study documented 1.2% SSI in Group 1 and 0.8% in Group 2 (p=0.742). Calculation of the incremental cost-effectiveness ratio found that an extra IDR 3,278,000 was needed to provide additional success to prevent SSI by administering multiple doses of ceftriaxone. In conclusion, a single dose prophylactic antibiotic provides comparable efficacy to a multiple-dose regimen, but at a lower cost.